Implication of Didikan Shubuh Program: An Analytical Study of MDTA Masjid Nurul Hidayah Pagambiran Padang City - Aldi, Muhammad; Khairanis, Retisfa (Quoba: Jurnal Pendidikan, 2024)
This study aims to analyze the implications of the implementation of the Didikan Subuh Program at MDTA Masjid Nurul Hidayah, Pagambiran, Padang City. The focus of the research includes the effectiveness of the program in improving Islamic understanding, Islamic character building, and strengthening students' spiritual values. This research uses a qualitative approach with a case study method. Data were collected through observation, in-depth interviews with teachers, mosque administrators, and students, and documentation studies. Data analysis was done descriptively with reduction, presentation, and conclusion techniques. The results showed that the Didikan Subuh Program has a significant positive impact in shaping Islamic character, especially in the aspects of discipline, honesty, and responsibility. The program is also effective in increasing community participation in religious activities, strengthening social relations in the mosque environment, and raising awareness of the importance of early religious education. The implication of this study is the need for more systematic curriculum development and active involvement of parents in supporting the success of the program. The contribution of this research is to provide insight to mosque managers and religious education institutions in optimizing similar programs in the community to strengthen Islamic values in the younger generation